Genomic and genetic advances of oiltea-camellia (Camellia oleifera) - Ye, Changrong; He, Zhilong; Peng, Jiayu; Wang, Rui; Wang, Xiangnan; Fu, Mengjiao; Zhang, Ying; Wang, Ai; Liu, Zhixian; Jia, Gaofeng; Chen, Yongzhong; Tian, Bingchuan (Frontiers in Plant Science, 2023)
Oiltea-camellia (C. oleifera) is an important woody oil crop widely cultivated in Southeast Asia and Southern China. The genome of oiltea-camellia was very complex and not well explored. Recently, genomes of three oiltea-camellia species were sequenced and assembled, multi-omic studies of oiltea-camellia were carried out and provided a better understanding of this important woody oil crop. In this review, we summarized recent findings on the reference genomes of oiltea-camellia and its relatives, genes related to economic traits and environmental stress tolerances, and multi-omic studies of oiltea-camellia. We also discussed future directions of integrating multiple omics evaluating genetic resources, and to identify key genes to accelerate the breeding process of oiltea-camellia.